PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. DUTA ANGKASA PRIMA KARGO TANGERANG - Rudini Raya Lambe; Hery Wihasnanto (Jurnal Ekonomi dan Industri, 2023)
Purpose to determine the effect of work environment and work discipline on employee performance of PT. Duta Angkasa Prima Kargo Tangerang. This research is included in the category of causal associative research using a quantitative approach. The population in this study are employees of PT. Duta Angkasa Prima Kargo Tangerang to 282 people. By using the Slovin formula, a sample of 74 employees of PT. Duta Angkasa Prima Kargo Tangerang. The research method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the work environment and work discipline had a positive and significant effect on employee performance of PT. Duta Angkasa Prima Kargo Tangerang.